ABOUT GUARANTEED CONTROL MATERIAL POINTS AT THE INCOMPLETE INFORMATION - Ghukasyan, A. A.; Manukian, A. A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
The problem of control of a material point when position of a target point is known with accuracy of some set is investigated and in process of approach is specified discretely. With application of the guaranteed approach the problem of synthesis, optimum reduction time for an ellipse and a piece is solved.